(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Wave cycloidal rotors are lift based wave energy devices that have shown great potential to harness the energy of the waves through the use of submerged hydrofoils. Although the lift force of the foils can be controlled passively or actively to maximise power extraction, the foils of the rotor are subject to variable loading which can expose these components to premature mechanical failure. Therefore, it is important to develop novel fatigue analysis tools that help predicting the lifetime of this type of lift based devices. In this paper, we test the hypothesis that when cyclorotor operates at constant rotational velocity in irregular waves, the fatigue damage of the hydrofoil stress hot spot can be computed through a probabilistic approach. We compare our results to the fatigue damage computed with well established deterministic methods. We find that for both narrow and broad band stress energy spectra, the probabilistic method works well at high probability sea states, when the range of stresses does not exceed the inflection point of a double slope SN curve. This is a promising outlook since it confirms that the fatigue damage of these versatile lift based wave devices can be treated in a similar fashion to the fatigue damage of conventional offshore structures.